Early predictors of language skills at 3 years of age vary based on diagnostic outcome: A baby siblings research consortium study. Issue 7 (1st June 2022) - Pecukonis, Meredith; Young, Gregory S.; Brian, Jessica; Charman, Tony; Chawarska, Katarzyna; Elsabbagh, Mayada; Iverson, Jana M.; Jeste, Shafali; Landa, Rebecca; Messinger, Daniel S.; Schwichtenberg, A. J.; Webb, Sara Jane; et al.
Abstract: While previous work has identified the early predictors of language skills in infants at elevated familial risk (ER) and low familial risk (LR) for autism spectrum disorder (ASD), no studies to date have explored whether these predictors vary based on diagnostic outcome of ASD or no ASD. The present study used a large, multisite dataset to examine associations between a set of commonly studied predictor variables (infant gesture abilities, fine motor skills, nonverbal cognition, and maternal education level), measured at 12 months, and language skills, measured at 3 years, across three diagnostic outcome groups–infants with ASD ("ASD"), ER infants without ASD ("ER‐no ASD"), and LR infants without ASD ("LR‐no ASD"). Findings revealed that the predictors of language skills differed across groups, as gesture abilities were positively associated with language skills in the ER‐no ASD group but negatively associated with language skills in the ASD group. Furthermore, maternal education level was positively associated with language skills in the ASD and LR‐no ASD groups only. Variability in these early predictors may help explain why language skills are heterogeneous across the autism spectrum, and, with further study, may help clinicians identify those in need of additional and/or specialized intervention services that support language development. Lay Summary: The present study identified predictors of language skills in infants with and without autism spectrum disorder (ASD). Maternal education level and 12‐month gesture abilities predicted 3‐year language skills in infants with ASD. Measuring these predictors early in life may help identify infants and families in need of additional and/or specialized intervention services that support language development.